Sodium-hydrogen exchanger, cardiac overload, and myocardial hypertrophy - Cingolani, Horacio Eugenio (2007)
Overload of neonatal and adult cardiomyocytes and multicellular myocardial preparations, which include whole hearts, are accompanied by an enhanced activity of the Na+/H+ exchanger 1 (NHE-1). Exogenous administration of prohypertrophic agents such as angiotensin II (Ang II), endothelin-1 (ET-1), and α1-adrenergic agonists also stimulates NHE-1 activity, which leads to an increased concentration of intracellular Na+ ([Na+]i). Moreover, inhibition of NHE-1 activity prevents the increase in [Na+]i, induces the regression of cardiac hypertrophy, and exerts beneficial effects in experimental heart failure. The present review summarizes the current knowledge of the causative factors and pathophysiological correlation of cardiac overload and NHE-1 activity.